PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT. CIPTA NIAGA SEMESTA - Rizki Bayu Permana; Ahmad Hermanto (Jurnal Ekonomi dan Industri, 2020)
The purpose of this study was to determine the effect of leadership and work motivation on the performance of employees of PT. Cipta Niaga Universe. The research method using descriptive analysis, linear regression analysis both partially and multiple The findings are that Leadership can encourage employee performance improvement, this can be seen from the ability to analyze the leader to supervise the work of subordinates, can provide direction, dare to rebuke subordinates if there are errors in work, the leader is willing to accept opinions and suggestions from subordinates, the leader is firm in his duties and faces subordinates. Work motivation can encourage improvement in employee performance, where a good work environment, salaries received by employees as expected, there are incentives for those who excel, there is work protection and company recognition of employee work performance.